Are old regions less attractive? Interregional labour migration in a context of population ageing - Paula Prenzel (Papers in Regional Science, 2021)
Regional demographic change is often conceptualized as a circular process, where out-migration continuously worsens conditions of population ageing and shrinkage. Thus, if migration acts as a consequence as well as cause of ageing, migration patterns should be influenced by the age structure of origin and destination regions. This paper analyses individual-level migration decisions of full-time employees across 326 German regions between 1997 and 2013 using binary choice models. The results show that individuals are more likely to migrate out of and less likely to migrate towards ageing regions. Moreover, the identified patterns are consistent with age-selective migration reinforcing ageing processes and polarization of demographic structure.
Keywords: 300; demographic change; interregional migration; regional polarization; selective migration